Himalayapotamon chambaensis, a new species of freshwater crab (Crustacea: Brachyura: Potamidae) from Himachal Pradesh, India - Mitra, Santanu; Valarmathi, Kandasamy (Zootaxa, 2017)
A new species of freshwater crab of the genus Himalayapotamon Pretzmann, 1966, is described based on specimens collected from various localities in Chamba District in Himachal Pradesh state, northern India. Himalayapotamon chambaensis n. sp. can be distinguished from congeners by several carapace and gonopod characters: a short median longitudinal granular ridge behind the frontal margin which reaches to the epigastric regions, the terminal segment of the male first gonopod is long and distinctly bent outwards, and the male second gonopod has a long and distally coiled distal segment. An identification key to all the 12 species in the genus is provided.